PENGEMBANGAN MODEL PEMBELAJARAN PERMAINAN HOCKEY CERIA DALAM PEMBELAJARAN PENJASORKES SMA NEGERI 1 BOJA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to produce a model of learning development that aims to increase student motivation motion for SMA Negeri 1 Boja . The method of research is the development of a model refers to the development of Brog and Gall : ( 1 ) to analyze the products that will be developed from the results of field observations and literature review , ( 2 ) developing the initial product form , ( 3 ) evaluation of experts ( 4 ) revision of the initial product , ( 5 ) large -scale field trials , ( 6 ) the revision of the final product after conducting field trials large scale , ( 7 ) the end result Cheers hockey game models on N 1 Boja high school students .. From the research data , the data that the expert evaluation , expert penjas 76 % ( good ) , 84 % of learning experts ( good ) , small -scale trials of the questionnaire obtained an average percentage of 82.33 corresponding answer choices % ( good ) . As for the large -scale field trials of the questionnaire the average percentage of the corresponding answer choice 84.89 % ( excellent ) . Based on the results above , it can be concluded that the model of the game " hockey Cheers " can be applied to high school students N 1 Boja . The end result of this is the development of research activitiesProducts Hockey game Cheerful learning model can already be put into practice to test subjects Products Hockey game Cheerful learning model can already be used for high school students 1 N Boja.